2014
DOI: 10.1002/rra.2738
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Fish Assemblage Structure in a Large River

Abstract: The Penobscot River drains the largest watershed in Maine and once provided spawning and rearing habitats to 11 species of diadromous fishes. The construction of dams blocked migrations of these fishes and likely changed the structure and function of fish assemblages throughout the river. The proposed removal of two main‐stem dams, improved upstream fish passage at a third dam, and construction of a fish bypass on a dam obstructing a major tributary is anticipated to increase passage of and improve habitat con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 36 publications
2
41
0
Order By: Relevance
“…We also observed a decline in relative biomass of adult Smallmouth Bass in the Orono stratum (Figure ), which may indicate that the former Veazie Dam impoundment served as local winter refugia habitat for adult fish, as was suggested by Kiraly et al. (2014a). The factors associated with these observed changes to resident fish assemblages are complex and likely associated with impoundments reverting to lotic habitats; however, we made no empirical measure of habitat change, and without such a measure, it is impossible to determine the specific mechanisms that drove the observed differences.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…We also observed a decline in relative biomass of adult Smallmouth Bass in the Orono stratum (Figure ), which may indicate that the former Veazie Dam impoundment served as local winter refugia habitat for adult fish, as was suggested by Kiraly et al. (2014a). The factors associated with these observed changes to resident fish assemblages are complex and likely associated with impoundments reverting to lotic habitats; however, we made no empirical measure of habitat change, and without such a measure, it is impossible to determine the specific mechanisms that drove the observed differences.…”
Section: Discussionsupporting
confidence: 78%
“…Kiraly et al. (2014a) found that Alewife was a significant indicator species in the Tidal stratum, and Smallmouth Bass and Pumpkinseed were both significant indicator species in the Orono stratum. We also examined the spatial distribution of American Eel Anguilla rostrata due to its status as a species of concern and its ubiquity in the watershed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Along with the results provided elsewhere (Bitušík et al, 2006;Krno, 2007;Illéšová et al, 2008) we obtained important information on predisturbance longitudinal patterns in benthic assemblages of the Hron River. Dams affect the sediment dynamics and distribution, dispersal, and abundance of benthic macroinvertebrates and other aquatic organisms (Stanford et al, 1996;Kiraly et al, 2014). Multiple damming of a river may result in longitudinal modifications towards upstream or (more likely) downstream abiotic and biotic conditions (Ward and Stanford, 1983b) and subsequently in alternation of spatial organisation of the whole river ecosystem.…”
Section: > River Zonation As a Reference Schemementioning
confidence: 99%